2016
DOI: 10.1097/md.0000000000005379
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous trigeminal ganglion radiofrequency thermocoagulation alleviates anxiety and depression disorders in patients with classic trigeminal neuralgia

Abstract: Trigeminal neuralgia (TN) is a neurological condition that presents as excruciating facial pain. Depression and anxiety are commonly associated with TN; however, anxiety and depression disorders in patients with TN and the effects of the various therapeutic strategies for TN on these disorders are not well studied.To evaluate depression and anxiety in patients with trigeminal neuralgia (TN), identify factors that predict their occurrence and study the effect of the percutaneous trigeminal ganglion radiofrequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…As far as we know, this is the first animal evidence that only 2 weeks of TN can induce behavioral despair. In line with this, some clinical studies have revealed that treatment of TN can immediately attenuate depressive disorders [40], and conversely, when a comorbid patient was treated with the antidepressant duloxetine, the TN was unexpectedly and rapidly relieved [41]. Together, these findings point out that neuralgia and depression might be modulated similarly.…”
Section: Discussionmentioning
confidence: 53%
“…As far as we know, this is the first animal evidence that only 2 weeks of TN can induce behavioral despair. In line with this, some clinical studies have revealed that treatment of TN can immediately attenuate depressive disorders [40], and conversely, when a comorbid patient was treated with the antidepressant duloxetine, the TN was unexpectedly and rapidly relieved [41]. Together, these findings point out that neuralgia and depression might be modulated similarly.…”
Section: Discussionmentioning
confidence: 53%
“…Active damaging of the nerves for the treatment of some diseases has been highly accepted by the patients. e definition of "effective" for the treatment of trigeminal neuralgia varied in different studies [21][22][23]. For instance, some studies have defined "effective" as pain remission by >50% after treatment [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical rhizotomy can be achieved through the use of trigeminal ganglion balloon compression [52]. Lastly, the causative sensory nerve fibers can be selectively destroyed by heat formed by percutaneous radiofrequency rhizotomy [53]. These various surgical procedures often provide immediate pain relief [54].…”
Section: Surgical Treatmentmentioning
confidence: 99%